2014
DOI: 10.1016/j.conbuildmat.2013.08.080
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of hollow core square reinforced concrete columns wrapped with CFRP with different fibre orientations

Abstract: Results of testing twelve hollow core square reinforced concrete columns wrapped with Carbon fibre 33 reinforced polymer (CFRP) are presented. The effect of fibre orientation on the performance of specimens 34 under concentric and eccentric loads was investigated. Twelve specimens were divided into four groups with three 36 specimens each. The specimens in the first reference group were unwrapped, while the specimens in the 37 remaining groups were wrapped with CFRP of different wrap combinations of three fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Hollow concrete columns (HCCs) are one of the preferred construction systems in civil infrastructures-including bridge piers, ground piles, and utility poles-to minimize the overall weight and reduce costs given the small amount of concrete in the column itself and the underlying foundations. HCCs are also considered a practical solution to increase the strengthto-mass ratio of structures compared to the solid concrete columns (Lignola, et al, 2007, Kusumawardaningsih and Hadi, 2010, Hadi and Le, 2014, Lee, et al, 2015. Designing an HCC with sufficient strength and reliable structural performance, however, requires careful consideration of some critical parameters, including lateral-reinforcement details and concrete compressive strength (Zahn, et al, 1990, Mo, et al, 2003, Lignola, et al, 2007, Lee, et al, 2015, Liang, et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Hollow concrete columns (HCCs) are one of the preferred construction systems in civil infrastructures-including bridge piers, ground piles, and utility poles-to minimize the overall weight and reduce costs given the small amount of concrete in the column itself and the underlying foundations. HCCs are also considered a practical solution to increase the strengthto-mass ratio of structures compared to the solid concrete columns (Lignola, et al, 2007, Kusumawardaningsih and Hadi, 2010, Hadi and Le, 2014, Lee, et al, 2015. Designing an HCC with sufficient strength and reliable structural performance, however, requires careful consideration of some critical parameters, including lateral-reinforcement details and concrete compressive strength (Zahn, et al, 1990, Mo, et al, 2003, Lignola, et al, 2007, Lee, et al, 2015, Liang, et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the confinement provided by FRP are achieved mainly when the column is loaded concentrically or when the load eccentricity is small (Li and Hadi 2003;Hadi 2006b;Hadi 2006a;Hadi 2007;Bisby and Ranger 2010). However, attaching FRP straps longitudinally on the columns enhances the flexural strength of columns under eccentric loading (Chaallal and Shahawy 2000;Hadi 2007;Fitzwilliam and Bisby 2010;Hadi and Widiarsa 2012;Hadi and Le 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades extensive studies have been conducted on the confinement of concrete columns with FRP sheets [19][20][21][22][23][24][25][26][27][28][29]. The experimental results revealed that confining concrete columns with FRP sheets can considerably improve the strength and ductility of concrete columns.…”
Section: Introductionmentioning
confidence: 99%